Dietary diversity and nutrient adequacy among women in Bosomtwe District, Ghana - Apprey, Charles; Addae, Hammond Yaw; Boateng, Grace; Aduku, Linda Esi; Annan, Reginald A. (Maternal & Child Nutrition, 2025)
An article published in Maternal & Child Nutrition 2024;e13757.; https://doi.org/10.1111/mcn.13757